Analisis Ujaran Kebencian dalam Kolom Komentar pada Media Sosial X, Tik Tok, dan Instagram - Nabila, Salma; Kharisma Agustya Zahra Salsabilla; Nathania Trixie Aryanti; Vira Adhelia Andjani; Alfina Zahrah Umardi; Eni Nurhayati (Yayasan Literasi Sains Indonesia, 2023)
With the advent of social media, the way people interact and communicate has changed. Social media can also make people speak or comment freely, which can have a negative impact on the person concerned. Behind the benefits provided, social media certainly has disadvantages, one of which is that it is often misused by irresponsible parties. Social media is often used as a medium for spreading hatred. The problem that often arises is the emergence of hate speech or hate speech, which is now increasingly prevalent. The purpose of this study is to find out which social media has the highest level of hate speech. Using a quantitative approach descriptive type, this study distributed questionnaires to respondents and and through direct analysis through social media accounts of Indonesian artists. The results showed that respondents often found hate speech in the comments section of TikTok and X, followed by Instagram. Bullying posted on social media is the most common type of speech found and the fastest spreading hate speech is on social media X.